Regulating the photoluminescence of aluminium complexes from non-luminescence to room-temperature phosphorescence by tuning the metal substituents - Shunichiro Ito; Takuya Hosokai; Kazuo Tanaka; Yoshiki Chujo (Communications Chemistry, 2024)
Abstract Although luminescent aluminum compounds have been utilized for emitting and electron transporting layers in organic light-emitting diodes, most of them often exhibit not phosphorescence but fluorescence with lower photoluminescent quantum yields in the aggregated state than those in the amorphous state due to concentration quenching. Here we show the synthesis and optical properties of β-diketiminate aluminum complexes, such as crystallization-induced emission (CIE) and room-temperature phosphorescence (RTP), and the substituent effects of the central element. The dihaloaluminum complexes were found to exhibit the CIE property, especially RTP from the diiodo complex, while the dialkyl ones showed almost no emission in both solution and solid states. Theoretical calculations suggested that undesired structural relaxation in the singlet excited state of dialkyl complexes should be suppressed by introducing electronegative halogens instead of alkyl groups. Our findings could provide a molecular design not only for obtaining luminescent complexes but also for achieving triplet-harvesting materials.